Heavy and light minerals at DSDP Leg 67 Holes - Prasad, Sachindra; Hesse, Reinhard (Supplement to: Prasad, S; Hesse, R (1982): Provenance of detrital sediments from the Middle America Trench transect off Guatemala, Deep Sea Drilling Project Leg 67. In: Abouin, J; von Huene, R; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 67, 507-514, https://doi.org/10.2973/dsdp.proc.67.118.1982, 1982)
Heavy and light minerals were examined in 29 samples from Sites 494, 498, 499, 500, and 495 on the Deep Sea Drilling Project Leg 67 Middle America Trench transect; these sites represent lower slope, trench, and oceanic crust environments off Guatemala. All samples are Quaternary except those from Hole 494A (Pliocene) and Hole 498A (Miocene). Heavy-mineral assemblages of the Quaternary sediments are characterized by an immature pyroxene-amphibole suite with small quantities of olivine and epidote. The Miocene sediments yielded an assemblage dominated by epidote and pyroxene but lacking olivine; the absence of olivine is attributed to selective removal of the most unstable components by intrastratal solution. Light-mineral assemblages of all samples are predominantly characterized by volcanic glass and plagioclase feldspar. The feldspar compositions are compatible with andesitic source rocks and frequently exhibit oscillatory zoning. The heavy- and light-mineral associations of these sediments suggest a proximal volcanic source, most probably the Neogene highland volcanic province of Guatemala. Sand-sized components from Site 495 are mainly biogenic skeletons and volcanic glass and, in one instance (Section 495-5-3), euhedral crystals of gypsum.